The white crow - Robotham, Michael, 1960- (Robotham, Michael, 1960- Philomena McCarthy series., 2025)
"Philomena McCarthy has defied the odds to become a young officer with the Metropolitan Police despite her father and her uncles being notorious London gangsters. On patrol one night, Philomena finds a barefoot child, covered in blood, who says she can't wake her mother. Meanwhile, three miles away, a London jeweler has a bomb strapped to his chest in his ransacked store and millions are missing. These two events collide and threaten Philomena's career, her new marriage, and her life. In too deep, and falling further, Phil must decide who she can trust-her family or her colleagues-and on what side of the thin blue line she wants to live. Told in real time from multiple points of view, The White Crow is filled with almost unbearable suspense-a page-turning tour de force that shows Robotham at the top of his game"--